Prevalence of comorbid substance use in schizophrenia spectrum disorders in community and clinical settings, 1990–2017: Systematic review and meta-analysis - Hunt, Glenn E.; Large, Matthew M.; Cleary, Michelle; Lai, Harry Man Xiong; Saunders, John B. (Drug and alcohol dependence, 2018)
•This review assessed prevalence of substance use in people with schizophrenia.•The prevalence of any substance use disorder (SUD) was 42%.•Meta-analysis showed substance use was higher in males (48%) than females (22%).•People with SUD had an earlier age of onset of schizophrenia.•Comorbid prevalence rates have not changed over time. Comorbidity is highly prevalent between substance use disorders (SUDs) and schizophrenia. This systematic review and meta-analysis estimated prevalence rates of SUDs in epidemiological and treatment-seeking patients diagnosed with schizophrenia or first episode psychosis. A literature search of Medline, EMBASE, PsycINFO and CINAHL databases was conducted from 1990 to 2017 inclusive. Prevalence of co-morbid SUDs and schizophrenia were extracted and odds ratios (ORs) were calculated using random effects meta-analysis. Combining like studies was dictated how authors reported substance use. There were 123 included articles with a total sample size of 165,811 subjects that yielded six epidemiological studies, 11 national or state case-registry studies, 20 large cohort studies and 86 clinical studies using in- or out-patient samples. The prevalence of any SUD was 41.7%, followed by illicit drugs (27.5%), cannabis (26.2%), alcohol (24.3%) and stimulant use (7.3%). Meta-analysis showed the pooled variance of any SUD in males was 48% which was significantly higher than that for females with schizophrenia (22.1%, OR 3.43, 95% CI 3.01, 3.92). Patients with SUD had an earlier age of onset of schizophrenia. Meta-regression showed prevalence increased over time for illicit drugs but not for other substances, including alcohol. The meta-analysis revealed that SUDs in schizophrenia is highly prevalent and rates have not changed over time. This indicates SUD are difficult to treat in this patient population and there is an urgent need for more informative studies to help develop better prevention, detection and treatment of SUDs in persons with schizophrenia and co-morbid disorders.